The complete mitochondrial genome of David's myotis, Myotis davidii (Myotis, Vespertilionidae). (3rd May 2016) - Wang, Shu-Qi; Li, Yan-Jiao; Yin, An-Guo; Zhang, Wei; Jiang, Jian-Jun; Wang, Wen-Lin; Hu, Min
Abstract: In this study, we report the complete mitochondrial genome sequence of David's myotis, Myotis davidii . The genome is found to be 17, 531 bp in length and has a base composition of A (33.8%), G (13.2%), C (23.2%), and T (29.8%). Similar to other bats, it contains a typically conserved structure including 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and 1 control region (D-loop). Most of the genes are encoded on H-strand, except for the ND6 subunit gene and 8 tRNA genes. All protein-coding genes start with an ATG codon except for ND2, ND3 and ND5, which initiate with ATT or ATA instead, and terminate with the typical stop codon (TAA/TAG) or a single T (T–) or an unexpected codon of AGA. The complete mitochondrial genome sequence provided here would be useful for further phylogenetic analysis and population genetic studies in M. davidii.